Composite fiber particles containing fibers and inorganic particles
By controlling the moisture ratio, the composite fiber particles are synthesized and processed, the problem of insufficient flowability and dispersion of composite fiber particles in the prior art is solved, and the effects of high flowability and high dispersion are achieved.
Patent Information
- Application Number
- CN202080053104.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-09-20
- Filing Date
- 2020-09-15
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2040-09-15
AI Technical Summary
It is difficult to develop composite fiber particles of fiber and inorganic particles in the prior art, and their fluidity and dispersion are insufficient.
By controlling the moisture content before and during granulation, composite fiber particles with particle sizes of 0.1 to 10 mm are synthesized and processed to ensure that their moisture content is less than 60% to improve fluidity and dispersion.
The composite fiber particles of fiber and inorganic particles have excellent fluidity and dispersion, making it easier to cooperate with other products and give it a high deodorization effect.
Smart Images

Figure CN114174388B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to composite fiber particles containing fibers and inorganic particles and a method for producing the same. Background Art
[0002] Composite fibers having various properties have been developed by attaching inorganic particles to the fiber surface. For example, it is known that inorganic particles are attached to the fiber surface by synthesizing an inorganic substance in the presence of a fiber.
[0003] For example, there are known composite fibers of calcium carbonate and fibers (Patent Document 1), composite fibers of magnesium carbonate and fibers (Patent Document 2), composite fibers of calcium phosphate and fibers (Patent Document 3), composite fibers of hydrotalcite and fibers (Patent Document 4), and composite fibers of silica / alumina and fibers (Patent Document 5).
[0004] In addition, composite fibers in which most of the fiber surface is coated with inorganic particles (Patent Document 6), composite fibers in which inorganic particles are attached to the fiber surface to improve flame retardancy (Patent Document 7), and the like have been reported.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: International Publication No. WO2015 / 152283
[0008] Patent Document 2: International Publication WO2017 / 043580
[0009] Patent Document 3: International Publication WO2017 / 043585
[0010] Patent Document 4: International Publication WO2018 / 030521
[0011] Patent Document 5: International Publication WO2019 / 163659
[0012] Patent Document 6: International Publication WO2017 / 057154
[0013] Patent Document 7: International Publication WO2019 / 159943 Summary of the invention
[0014] An object of the present invention is to provide particles including composite fibers of fibers and inorganic particles and having excellent fluidity.
[0015] The present inventors have conducted intensive studies on the above-mentioned problems and, as a result, have found that excellent granules can be obtained by controlling the moisture content before and during granulation, thereby completing the present invention.
[0016] That is, the present invention includes the following aspects, but is not limited thereto.
[0017] [1] A particle comprising composite fibers of fibers and inorganic particles, with a particle size of 0.1 to 10 mm and a moisture content of less than 60%.
[0018] [2] The particles according to [1], wherein the angle of repose is 30 to 58°.
[0019] [3] The particles according to [1] or [2], wherein the inorganic particles include a metal salt of calcium, magnesium, barium or aluminum, a metal particle including titanium, copper or zinc, or a silicate.
[0020] [4] The particle according to any one of [1] to [3], wherein the inorganic particle is hydrotalcite.
[0021] [5] The particle according to any one of [1] to [4], wherein the weight ratio of the inorganic particles in the particle is 10% or more.
[0022] [6] The particles according to any one of [1] to [5], wherein the fibers are cellulose fibers.
[0023] [7] The particle according to any one of [1] to [6], wherein 15% or more of the fiber surface is covered with inorganic particles.
[0024] [8] A method for producing the particles described in any one of [1] to [7], comprising: a step of synthesizing inorganic particles in a liquid containing fibers to obtain composite fibers; and a step of granulating the composite fibers into particles having a particle size of 0.1 to 10 mm.
[0025] [9] The method according to [8], wherein in the granulation step, the composite fibers are granulated while being dried.
[0026]
[10] The method according to [8], wherein the granulation is performed after the moisture content of the composite fiber is reduced to less than 60%.
[0027]
[11] The method according to [8], wherein the composite fibers are granulated after being pulverized.
[0028] According to the present invention, it is possible to obtain particles obtained by processing composite fibers of fibers and inorganic particles into granules. The obtained particles are excellent in fluidity and dispersibility, and therefore can be easily matched with other products to impart functionality corresponding to the characteristics of the inorganic particles to the other products. In particular, when inorganic particles with high deodorizing effects are used, particles with high deodorizing effects can be obtained. In addition, by using composite fibers of fibers and inorganic particles as the raw materials of the particles, it is possible to suppress the amount of inorganic particles to be matched and impart functionality corresponding to the characteristics of the inorganic particles. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a schematic diagram of the production apparatus used in Experiment 1 (P: pump).
[0030] Figure 2 This is an electron microscope photograph of sample a (magnification: 3000 times).
[0031] Figure 3 This is an electron microscope photograph of sample b (magnification: 3000 times).
[0032] Figure 4 This is an electron microscope photograph of sample c (magnification: 3000 times).
[0033] Figure 5 This is an electron microscope photograph of sample d (magnification: 3000 times).
[0034] Figure 6 This is an electron microscope photograph of sample f (magnification: 3000 times).
[0035] Figure 7 This is a photograph of the appearance of Sample 1 of Experiment 2. DETAILED DESCRIPTION
[0036] The present invention relates to particles of composite fibers containing fibers and inorganic particles. Particles refer to particles generally having a larger particle size than powders, and the particle size is 0.1 mm or more. The particles of the composite fibers of the present invention can be obtained, for example, by solidifying the powder and molding it into slightly larger particles. If necessary, the particles can also be dried and water can be added to adjust the water content (solid content). Composite fibers of fibers and inorganic particles are sometimes obtained in a state with a high water content. In this case, the composite fibers can be dried and molded into slightly larger particles to produce particles. Particles have little concern about generating dust like powders or coagulating when water is added to prevent dissolution. In addition, compared with composite fibers in the form of aqueous suspensions or pulp, they have the advantage of being easily dispersed in other products.
[0037] There is no particular limitation on the dryer used when drying the composite fiber of the synthetic fiber and the inorganic particles. For example, an air flow dryer, a belt dryer, a spray dryer, a vacuum dryer, a low-temperature dryer, a rotary dryer, a professional shear mixer, an oven, etc. can be appropriately used. Among them, it is easy to produce particles of a target particle size from the composite fiber using a device such as a professional shear mixer that can simultaneously perform drying and granulation, so it is preferred. In addition, in the present invention, the composite fiber can also be granulated after being micronized.
[0038] Water can be added dropwise from a dedicated pipe or a pipeline installed as needed. The liquid to be added can be water (industrial water, tap water, distilled water, ultrapure water), a solution of metal ions, a dispersion of starch or CMC, a solution to which anionic, cationic, or nonionic agents are added, etc., as appropriate according to the application.
[0039] In the present invention, the particle size of the particles is 0.1 mm to 10 mm. The particle size of the particles is preferably 0.2 mm to 4 mm, more preferably 0.3 mm to 3 mm, and the particle size of the particles can also be 0.5 mm to 2 mm. If the particle size is too small, the particles are easy to scatter, and if the particle size is too large, it is difficult to disperse when mixed with other raw materials.
[0040] The moisture content (water concentration) before granulation can be, for example, 0 to 80%, preferably 2 to 70%, more preferably 4 to 60%, and particularly preferably 6 to 50%. If the moisture content before granulation is too much, drying will take a long time and the efficiency will decrease. On the other hand, if the moisture content before granulation is too low, it will be difficult to evenly disperse the raw materials depending on the device for processing into granules. Therefore, moderate inclusion of moisture is suitable for the manufacture of granules.
[0041] The water content of the granules of the present invention is less than 60%. In a preferred embodiment, the water content of the granules is less than 45%, and may be less than 30%. By reducing the water content of the granules, the fluidity of the granules can be improved.
[0042] The particles of the present invention have excellent fluidity and are easy to handle. In a preferred embodiment, the repose angle of the particles of the present invention is 30 to 58°, more preferably 32 to 50°, and particularly preferably 34 to 40°. Particles with a small repose angle can be obtained by reducing the water content of the particles or adjusting the particle size of the particles.
[0043] Synthesis of composite fibers
[0044] In the present invention, composite fibers can be synthesized by synthesizing inorganic particles in a solution containing fibers such as cellulose fibers. The fiber surface becomes a suitable place for the precipitation of inorganic particles, and composite fibers are easily synthesized. As a method for synthesizing composite fibers, for example, a solution containing precursors of fibers and inorganic particles can be stirred and mixed in an open reaction tank to synthesize a composite, or an aqueous suspension containing precursors of fibers and inorganic particles can be sprayed into a reaction vessel to synthesize. As described later, when an aqueous suspension of an inorganic precursor is sprayed into a reaction vessel, cavitation bubbles can be generated, and inorganic particles can be synthesized in the presence of cavitation bubbles. Inorganic particles can be synthesized on cellulose fibers by known reactions, respectively.
[0045] In general, it is known that the generation of inorganic particles goes through a process from a cluster state (repeated aggregation and dispersion at a stage where the number of aggregated atoms and molecules is small) to a nucleus (transformation from a cluster to a stable aggregate state, when the atoms and molecules captured are not dispersed when the critical size is reached or above), and then growth (new atoms and molecules gather at the nucleus to make the particle larger). It is believed that the higher the raw material concentration and the reaction temperature, the easier it is for the nucleus to be generated. The composite fiber of the present invention is mainly obtained by adjusting the raw material concentration, the beating degree of pulp (specific surface area), the viscosity of the solution containing the fiber, the concentration and addition rate of the added chemical reagent, the reaction temperature, and the stirring rate so that the nucleus is effectively bonded to the fiber and the particle growth is promoted, thereby obtaining a composite fiber in which the surface of the cellulose fiber is firmly covered with inorganic particles.
[0046] In the present invention, the liquid can be sprayed under the condition that cavitation bubbles are generated in the reaction container, or it can be sprayed under the condition that cavitation bubbles are not generated. In addition, in either case, the reaction container is preferably a pressure container. It should be noted that the pressure container of the present invention refers to a container that can apply a pressure of more than 0.005MPa. Under the condition that cavitation bubbles are not generated, the pressure in the pressure container is preferably 0.005MPa to 0.9MPa in terms of static pressure.
[0047] (cavitation bubbles)
[0048] When synthesizing the composite fiber of the present invention, inorganic particles can be precipitated in the presence of cavitation bubbles. In the present invention, cavitation refers to a physical phenomenon in which bubbles are generated and disappear in a short period of time due to a pressure difference in the flow of a fluid, and is also called a cavitation phenomenon. Bubbles generated by cavitation (cavitation bubbles) are generated when the pressure in the fluid becomes lower than the saturated vapor pressure in a very short time, using extremely tiny "bubble nuclei" of less than 100 microns existing in the liquid as nuclei.
[0049] In the present invention, cavitation bubbles can be generated in the reaction vessel using known methods. For example, it is conceivable to generate cavitation bubbles by injecting a fluid at high pressure, generate cavitation by stirring at high speed in a fluid, generate cavitation by explosion in a fluid, generate cavitation using an ultrasonic vibrator (vibration-type cavitation), etc.
[0050] In the present invention, both can directly use reaction solution such as raw material as jet liquid and produce cavitation, also can spray some fluid in reaction vessel and produce cavitation bubble.As long as the fluid that liquid jet forms jet is in flowing state, just can be any one in solid such as liquid, gas, powder or pulp, in addition, also can be their mixture.If further need, then can add another kind of fluid such as carbon dioxide as new fluid in above-mentioned fluid.Above-mentioned fluid and new fluid can mix evenly and spray, also can spray respectively.
[0051] Liquid jet is a jet of fluid in which liquid or solid particles or gas are dispersed or mixed in liquid, and refers to a liquid jet containing pulp, raw material slurry of inorganic particles, and bubbles. The gas mentioned here may also include bubbles generated by cavitation.
[0052] Cavitation occurs when a liquid is accelerated and the local pressure becomes lower than the vapor pressure of the liquid, so flow rate and pressure are particularly important. Therefore, the basic dimensionless number representing the cavitation state, the cavitation number (Cavitation Number) σ, is preferably 0.001 to 0.5, preferably 0.003 to 0.2, and particularly preferably 0.01 to 0.1. When the cavitation number σ is less than 0.001, the pressure difference with the surroundings is low when the cavitation bubble collapses, so the effect becomes small. When it is greater than 0.5, the pressure difference of the flow makes it difficult to produce cavitation.
[0053] In addition, when cavitation is generated by spraying the injection liquid through a nozzle or a hole tube, the pressure of the injection liquid (upstream pressure) is ideally 0.01MPa to 30MPa, preferably 0.7MPa to 20MPa, and more preferably 2MPa to 15MPa. If the upstream pressure is less than 0.01MPa, it is not easy to produce a pressure difference with the downstream pressure, and the effect is small. In addition, when it is higher than 30MPa, a special pump and a pressure vessel are required, and the energy consumption becomes large, so it is disadvantageous in terms of cost. On the other hand, the pressure in the container (downstream pressure) is preferably 0.005MPa to 0.9MPa in terms of static pressure. In addition, the ratio of the pressure in the container to the pressure of the injection liquid is preferably in the range of 0.001 to 0.5.
[0054] In the present invention, the inorganic particles can also be synthesized by spraying the injection liquid under the condition that cavitation bubbles are not generated. Specifically, the pressure of the injection liquid (upstream pressure) is set to 2 MPa or less, preferably 1 MPa or less, and the pressure of the injection liquid (downstream pressure) is opened, more preferably 0.05 MPa or less.
[0055] The speed of the jet of the injection liquid is preferably in the range of 1m / second to 200m / second, preferably in the range of 20m / second to 100m / second. When the speed of the jet is less than 1m / second, the pressure drop is small and cavitation is not easy to occur, so its effect is weak. On the other hand, when it is greater than 200m / second, high pressure is required and a special device is required, which is disadvantageous in cost.
[0056] The cavitation generating site in the present invention can be generated in the reaction vessel for synthesizing inorganic particles. In addition, the cavitation generating site can be processed once or circulated as many times as required. Multiple generating mechanisms can also be used to process in parallel or in series.
[0057] The injection of the liquid for generating cavitation may be performed in a container open to the atmosphere, but is preferably performed in a pressure container in order to control cavitation.
[0058] When cavitation is produced by liquid jet, the solid component concentration of the reaction solution is preferably below 30 % by weight, more preferably below 20 % by weight. This is because if such a concentration is used, cavitation bubbles are easily made to play a role uniformly in the reaction system. In addition, from the aspect of reaction efficiency, the solid component concentration of the aqueous suspension of slaked lime as the reaction solution is preferably more than 0.1 % by weight.
[0059] In the present invention, for example, under the situation of the composite of synthetic calcium carbonate and cellulose fiber, the pH of reaction solution is alkaline side when reaction starts, but becomes neutral along with carrying out carbonation reaction.Therefore, can control reaction by monitoring the pH of reaction solution.
[0060] In the present invention, by increasing the injection pressure of the liquid, the flow rate of the injection liquid increases, and with this, the pressure drops, and more powerful cavitation can be produced. In addition, by pressurizing the pressure in the reaction container, the pressure in the area where the cavitation bubbles burst becomes higher, and the pressure difference between the bubbles and the surroundings becomes larger, so the bubbles burst violently and the impact force can be increased. Furthermore, the dissolution and dispersion of the introduced carbon dioxide can be promoted. The reaction temperature is preferably 0°C to 90°C, and particularly preferably 10°C to 60°C. In general, it is believed that the impact force is the greatest at the midpoint between the melting point and the boiling point, so in the case of an aqueous solution, it is preferably around 50°C, but even at a temperature below it, it is not affected by the vapor pressure, so a high effect can be obtained as long as it is within the above range.
[0061] When manufacturing the composite fiber of the present invention, various known auxiliary agents may be further added. For example, a chelating agent may be added, specifically, polyhydroxycarboxylic acids such as citric acid, malic acid, and tartaric acid, dicarboxylic acids such as oxalic acid, sugar acids such as gluconic acid, aminopolycarboxylic acids such as iminodiacetic acid and ethylenediaminetetraacetic acid and their alkali metal salts, alkali metal salts of polyphosphoric acids such as hexametaphosphoric acid and tripolyphosphoric acid, amino acids such as glutamic acid and aspartic acid and their alkali metal salts, ketones such as acetylacetone, methyl acetoacetate, and allyl acetoacetate, sugars such as sucrose, and polyols such as sorbitol. In addition, as surface treatment agents, saturated fatty acids such as palmitic acid and stearic acid, unsaturated fatty acids such as oleic acid and linoleic acid, alicyclic carboxylic acids, resin acids such as abietic acid, their salts, esters and ethers, alcohol-based activators, sorbitan fatty acid esters, amides, amine-based surfactants, polyoxyalkylene alkyl ethers, polyoxyethylene nonylphenyl ether, sodium α-olefin sulfonate, long-chain alkyl amino acids, amine oxides, alkylamines, quaternary ammonium salts, aminocarboxylic acids, phosphonic acid, polycarboxylic acids, condensed phosphoric acid, etc. can be added. In addition, dispersants can also be used as needed. As the dispersant, for example, sodium polyacrylate, sucrose fatty acid esters, glycerol fatty acid esters, acrylic acid-maleic acid copolymer ammonium salts, methacrylic acid-naphthyloxy polyethylene glycol acrylate copolymers, methacrylic acid-polyethylene glycol monomethacrylate copolymer ammonium salts, polyethylene glycol monoacrylate, etc. are provided. They can be used alone or in combination with multiple uses. In addition, the timing of addition can be before the synthesis reaction or after the synthesis reaction. Such additives can be added in an amount preferably of 0.001 to 20%, more preferably 0.1 to 10%, relative to the inorganic particles. In addition, in the present invention, the reaction can be an intermittent reaction or a continuous reaction. Generally speaking, from the convenience of discharging the residue after the reaction, it is preferred to carry out an intermittent reaction process. The scale of the reaction is not particularly limited, and the reaction can be carried out on a scale of less than 100 L, or on a scale exceeding 100 L. The size of the reaction container can be, for example, about 10 L to 100 L, or about 100 L to 1000 L.
[0062] In addition, the reaction can be controlled by utilizing the conductivity of the reaction solution and the reaction time. Specifically, the reaction can be controlled by adjusting the time the reactants are retained in the reaction tank. In addition, in the present invention, the reaction can also be controlled by stirring the reaction solution in the reaction tank or making the reaction a multi-stage reaction.
[0063] In the present invention, since the composite fiber as the reaction product is obtained in the form of a suspension, it can be stored in a storage tank as needed, or subjected to treatments such as concentration, dehydration, crushing, classification, aging, and dispersion. They can adopt known processes, as long as they are appropriately determined in consideration of the purpose, energy efficiency, etc. For example, the concentration and dehydration treatment is carried out using a centrifugal dehydrator, a sedimentation concentrator, etc. As examples of the centrifugal dehydrator, decanters, spiral decanters, etc. can be cited. In the case of using a filter or a dehydrator, there is no particular limitation on the type, and a general filter or dehydrator can be used. For example, a pressure-type dehydrator such as a filter press, a drum filter, a belt press, a tube press, a vacuum drum dehydrator such as an Oliver filter, etc. can be appropriately used to make a calcium carbonate filter cake. As the method of pulverization, ball mill, sand mill, impact mill, high pressure homogenizer, low pressure homogenizer, DYNO mill, ultrasonic mill, KANDA grinder, grinder, stone mortar grinder, vibration mill, chopper, jet mill, disintegrator, beater, short shaft extruder, double shaft extruder, ultrasonic mixer, household juicer, etc. can be mentioned. As the method of classification, sieves such as wire mesh, external or internal slit or round hole sieves, vibrating sieves, heavy foreign matter cleaners, light foreign matter cleaners, reverse cleaners, screening testers, etc. can be mentioned. As the method of dispersion, high speed disperser, low speed kneader, etc. can be mentioned.
[0064] The composite fiber of the present invention may be mixed with fillers and pigments in a suspension state without being completely dehydrated, or may be dried to form a powder. There is no particular limitation on the dryer used in this case, and for example, an airflow dryer, a belt dryer, a spray dryer, etc. may be appropriately used.
[0065] The composite fiber of the present invention can be modified by a known method. For example, in a certain embodiment, the surface of the composite fiber can be hydrophobized to improve the miscibility with resins and the like.
[0066] In the present invention, water is used in the preparation of the suspension, and as the water, ordinary tap water, industrial water, groundwater, well water, etc. can be used. In addition, ion exchange water, distilled water, ultrapure water, industrial waste water, and water obtained by separating and dehydrating the reaction solution can be appropriately used.
[0067] In addition, in the present invention, the reaction solution in the reaction tank can be circulated and used. By circulating the reaction solution in this way, stirring of the solution is promoted, and the reaction efficiency is easily improved to obtain a desired composite of inorganic particles and fibers.
[0068] Inorganic particles
[0069] In the present invention, the inorganic particles composited with the fiber are not particularly limited, but are preferably inorganic particles that are insoluble or poorly soluble in water. Inorganic particles are sometimes synthesized in an aqueous system, and fiber composites are sometimes used in an aqueous system, so it is preferred that the inorganic particles are insoluble or poorly soluble in water.
[0070] The inorganic particles mentioned here refer to compounds of metal elements or non-metal elements. Metal element compounds refer to metal cations (such as Na + , Ca 2+ Mg 2+ 、Al 3+ , Ba 2+ etc.) and anions (such as O 2- OH - 、CO3 2- PO4 3- 、SO4 2- 、NO3-、Si2O3 2- 、SiO3 2- , Cl - 、F - , S 2- The compound formed by bonding of metals such as metal oxides (such as metal oxides) and metal oxides (such as metal oxides) by ionic bonds is generally referred to as an inorganic salt. The compound of a non-metallic element refers to silicate (SiO2) and the like. In the present invention, it is preferred that at least a portion of the inorganic particles is a metal salt of calcium, magnesium or barium, or at least a portion of the inorganic particles is a metal salt of silicate or aluminum, or contains metal particles of titanium, copper, silver, iron, manganese, cerium or zinc.
[0071] The synthesis method of these inorganic particles can utilize known methods, and can be any one of gas-liquid method and liquid-liquid method.As an example of gas-liquid method, there is carbon dioxide method, for example, magnesium carbonate can be synthesized by reacting magnesium hydroxide with carbon dioxide.As an example of liquid-liquid method, acid (hydrochloric acid, sulfuric acid, etc.) and alkali (sodium hydroxide, potassium hydroxide, etc.) can be cited to react by neutralization, or inorganic salt and acid or alkali reaction, or inorganic salt reacts with each other.For example, barium sulfate can be obtained by reacting barium hydroxide with sulfuric acid, or aluminum hydroxide can be obtained by reacting aluminum sulfate with sodium hydroxide, or calcium and aluminum composite inorganic particles can be obtained by reacting calcium carbonate with aluminum sulfate.In addition, when synthesizing inorganic particles in this way, any metal or non-metallic compound can also be coexisted in the reaction solution, and at this time, these metals or non-metallic compounds can be efficiently introduced into the inorganic particles and composited.For example, when phosphoric acid is added to calcium carbonate and calcium phosphate is synthesized, by coexisting titanium dioxide in the reaction solution, the composite particles of calcium phosphate and titanium can be obtained.
[0072] (Calcium Carbonate)
[0073] In the case of synthesizing calcium carbonate, calcium carbonate can be synthesized by, for example, a carbon dioxide method, a soluble salt reaction method, a lime·caustic soda method, a caustic soda method, etc. In a preferred embodiment, calcium carbonate is synthesized by a carbon dioxide method.
[0074] Generally speaking, when utilizing the carbon dioxide method to make calcium carbonate, obtain slaked lime Ca(OH) by using lime (lime) as a calcium source and adding water in quicklime CaO slaked lime slaked lime Ca(OH) sludge process and blow carbon dioxide CO into slaked lime slaked lime and obtain calcium carbonate CaCO slaked lime process to synthesize calcium carbonate. At this moment, the suspension of slaked lime prepared by adding water in quicklime can be removed by sieve with the lime particles of low solubility contained in the suspension. In addition, also slaked lime can be directly used as a calcium source. In the present invention, when utilizing the carbon dioxide method to synthesize calcium carbonate, also can carry out carbonation reaction in the presence of cavitation bubbles.
[0075] When utilizing the carbon dioxide method to synthesize calcium carbonate, the solid component concentration of the aqueous suspension of slaked lime is preferably 0.1~40 weight %, more preferably 0.5~30 weight %, further preferably about 1~20 weight %. If the solid component concentration is low, then the reaction efficiency is low, and the manufacturing cost becomes high, and if the solid component concentration is too high, then the fluidity variation, and the reaction efficiency reduces. In the present invention, due to synthesizing calcium carbonate in the presence of cavitation bubbles, therefore, even if the high suspension (slurry) of solid component concentration is used, reaction solution and carbon dioxide can be suitably mixed.
[0076] As an aqueous suspension containing slaked lime, an aqueous suspension generally used in calcium carbonate synthesis can be used, for example, slaked lime can be mixed in water and prepared, or quicklime (calcium oxide) can be prepared by water digestion (digestion). The conditions during digestion are not particularly limited, for example, the concentration of CaO can be more than 0.05% by weight, preferably more than 1% by weight, and the temperature can be 20 to 100°C, preferably 30 to 100°C. In addition, the average residence time in the digestion reaction tank (digester) is not particularly limited either, for example, it can be 5 minutes to 5 hours, preferably within 2 hours. Of course, the digester can be intermittent or continuous. It should be noted that in the present invention, the carbonation reaction tank (carbonator) and the digestion reaction tank (digester) can be separated, and in addition, a reaction tank can also be used as a carbonation reaction tank and a digestion reaction tank.
[0077] In the synthesis of calcium carbonate, the higher the concentration of the raw materials (Ca ions, CO3 ions) in the reaction solution, and the higher the temperature conditions, the easier the nucleation reaction is to proceed. However, in the case of manufacturing composite fibers, under such conditions, it is not easy to fix the nucleus to the cellulose fiber, and it is easy to synthesize inorganic particles free in the suspension. Therefore, in order to manufacture composite fibers firmly bonded with calcium carbonate, it is necessary to properly control the nucleation reaction. Specifically, this can be achieved by rationalizing the concentration of Ca ions and pulp and smoothing the supply of CO2 per unit time. For example, the Ca ion concentration in the reaction vessel is preferably 0.01mol / L or more and less than 0.20mol / L. If it is less than 0.01mol / L, the reaction is not easy to proceed. If it is more than 0.20mol / L, it is easy to synthesize inorganic particles free in the suspension. The pulp concentration is preferably 0.5% or more and less than 4.0%. If it is less than 0.5%, the frequency of collision between the raw material and the fiber is reduced, so the reaction is not easy to proceed. If it is more than 4.0%, a uniform composite cannot be obtained due to poor stirring. The supply rate of CO2 per unit time is preferably 0.001 mol / min or more and less than 0.060 mol / min per 1 L of reaction solution. If it is less than 0.001 mol / min, the reaction is not easy to proceed, and if it is 0.060 mol / min or more, it is easy to synthesize inorganic particles free in the suspension.
[0078] (Magnesium carbonate)
[0079] In the case of synthesizing magnesium carbonate, the synthesis method of magnesium carbonate can utilize a known method. For example, magnesium bicarbonate can be synthesized from magnesium hydroxide and carbon dioxide, and basic magnesium carbonate can be synthesized from magnesium bicarbonate through magnesium orthocarbonate. Magnesium carbonate can be obtained by a synthetic method to obtain magnesium bicarbonate, orthomagnesium carbonate, basic magnesium carbonate, etc., and the magnesium carbonate of the fiber composite of the present invention is particularly preferably basic magnesium carbonate. This is because the stability of magnesium bicarbonate is relatively low, and the orthomagnesium carbonate of columnar (needle-shaped) crystals is sometimes not easy to fix on the fiber. On the other hand, by carrying out a chemical reaction in the presence of the fiber until basic magnesium carbonate is generated, a fiber composite of magnesium carbonate and the fiber with the surface of the fiber coated in a scale-like manner can be obtained.
[0080] In addition, in the present invention, the reaction solution in the reaction tank can be circulated and used. By circulating the reaction solution in this way, the contact between the reaction solution and carbon dioxide is increased, and the reaction efficiency is easily improved to obtain the desired inorganic particles.
[0081] In the present invention, a gas such as carbon dioxide (carbon dioxide gas) can be blown into the reaction container and mixed with the reaction solution. According to the present invention, carbon dioxide can be supplied to the reaction solution even without a gas supply device such as a fan or a blower, and carbon dioxide can be micronized by cavitation bubbles, so that the reaction can be carried out efficiently.
[0082] In the present invention, the carbon dioxide concentration of the gas containing carbon dioxide is not particularly limited, but preferably the carbon dioxide concentration is high. In addition, the amount of carbon dioxide introduced into the syringe is not limited and can be appropriately selected.
[0083] The gas that comprises carbon dioxide of the present invention can be pure carbon dioxide in fact, can also be a mixture with other gases.For example, except carbon dioxide, can also use the gas that comprises inert gases such as air, nitrogen as the gas that comprises carbon dioxide.In addition, as the gas that comprises carbon dioxide, except carbon dioxide (carbon dioxide), can also suitably use the waste gas discharged from the incinerator of paper mill, coal-fired boiler, heavy oil boiler etc. as the gas containing carbon dioxide.In addition, can also use the carbon dioxide produced by lime calcining process to carry out carbonation reaction.
[0084] In the synthesis of magnesium carbonate, the higher the concentration of raw materials (Mg ions, CO3 ions) in the reaction solution, and the higher the temperature conditions, the easier the nucleation reaction is to proceed. However, in the case of manufacturing composite fibers, under such conditions, it is not easy to fix the core to the cellulose fiber, and it is easy to synthesize inorganic particles free in the suspension. Therefore, in order to manufacture composite fibers firmly bonded with magnesium carbonate, it is necessary to properly control the nucleation reaction. Specifically, this can be achieved by rationalizing the concentration of Mg ions and pulp and smoothing the supply rate per unit time of CO2. For example, the Mg ion concentration in the reaction vessel is preferably 0.0001mol / L or more and less than 0.20mol / L. If it is less than 0.0001mol / L, the reaction is not easy to proceed. If it is more than 0.20mol / L, it is easy to synthesize inorganic particles free in the suspension. The pulp concentration is preferably 0.5% or more and less than 4.0%. If it is less than 0.5%, the frequency of collision between the raw material and the fiber is reduced, so the reaction is not easy to proceed. If it is more than 4.0%, a uniform composite cannot be obtained due to poor stirring. The supply rate of CO2 per unit time is preferably 0.001 mol / min or more and less than 0.060 mol / min per 1 L of reaction solution. If it is less than 0.001 mol / min, the reaction is not easy to proceed, and if it is 0.060 mol / min or more, it is easy to synthesize inorganic particles free in the suspension.
[0085] (Barium Sulfate)
[0086] In the case of synthetic barium sulfate, it is an ionic crystalline compound composed of barium ions and sulfate ions represented by barium sulfate (BaSO4), which is mostly in the form of plates or columns and is poorly soluble in water. Pure barium sulfate is a colorless crystal, but if it contains impurities such as iron, manganese, strontium, and calcium, it is yellowish brown or dark gray and becomes translucent. It can also be obtained in the form of natural minerals, but it can also be synthesized by chemical reactions. In particular, synthetic products obtained by chemical reactions are widely used in coatings, plastics, batteries, etc. in addition to being used for medical purposes (X-ray contrast agents), and their chemically stable properties are also used.
[0087] In the present invention, a composite of barium sulfate and fiber can be produced by synthesizing barium sulfate in a solution in the presence of fiber. For example, a method of reacting an acid (sulfuric acid, etc.) and a base by neutralization, or reacting an inorganic salt with an acid or a base, or reacting inorganic salts with each other can be cited. For example, barium sulfate can be obtained by reacting barium hydroxide with sulfuric acid or aluminum sulfate, or barium sulfate can be precipitated by adding barium chloride to an aqueous solution containing sulfate.
[0088] In the synthesis of barium sulfate, the higher the concentration of the raw materials (Ba ions, SO4 ions) in the solution, and the higher the temperature, the easier the nucleation reaction is to proceed. However, in the case of manufacturing composite fibers, under such conditions, it is not easy to fix the nucleus to the cellulose fiber, and it is easy to synthesize inorganic particles free in the suspension. Therefore, in order to manufacture composite fibers firmly bonded with barium sulfate, it is necessary to properly control the nucleation reaction. Specifically, this can be achieved by rationalizing the concentration of Ba ions and pulp and smoothing the supply of SO4 ions per unit time. For example, the Ba ion concentration in the reaction vessel is preferably 0.01 mol / L or more and less than 0.20 mol / L. If it is less than 0.01 mol / L, the reaction is not easy to proceed. If it is 0.20 mol / L or more, it is easy to synthesize inorganic particles free in the suspension. The pulp concentration is preferably 0.5% or more and less than 4.0%. If it is less than 0.5%, the frequency of collision between the raw material and the fiber is reduced, so the reaction is not easy to proceed. If it is 4.0% or more, a uniform composite cannot be obtained due to poor stirring. The supply rate of SO4 ions per unit time is preferably 0.005 mol / min or more and less than 0.080 mol / min per 1 L of reaction solution. If it is less than 0.001 mol / min, the reaction is difficult to proceed, and if it is 0.080 mol / min or more, it is easy to synthesize inorganic particles free in the suspension.
[0089] (Hydrotalcite)
[0090] In the case of synthesizing hydrotalcite, the synthesis method of hydrotalcite can utilize a known method. For example, in a reaction vessel, the fiber is immersed in a carbonate aqueous solution and an alkaline solution (sodium hydroxide, etc.) containing carbonate ions constituting the middle layer, and then an acid solution (a metal salt aqueous solution containing divalent metal ions and trivalent metal ions constituting the basic layer) is added, and the temperature, pH, etc. are controlled to synthesize hydrotalcite by coprecipitation reaction. In addition, the fiber can also be immersed in an acid solution (a metal salt aqueous solution containing divalent metal ions and trivalent metal ions constituting the basic layer) in a reaction vessel, and then, a carbonate aqueous solution and an alkaline solution (sodium hydroxide, etc.) containing carbonate ions constituting the middle layer are added dropwise, and the temperature, pH, etc. are controlled to synthesize hydrotalcite by coprecipitation reaction. It is usually a reaction under normal pressure, but in addition to this, there is also a method obtained by a hydrothermal reaction using an autoclave, etc. (Japanese Patent Publication No. 60-6619).
[0091] In the present invention, various chlorides, sulfides, nitrates, and sulfates of magnesium, zinc, barium, calcium, iron, copper, cobalt, nickel, and manganese can be used as the supply source of divalent metal ions constituting the basic layer. In addition, various chlorides, sulfides, nitrates, and sulfates of aluminum, iron, chromium, and gallium can be used as the supply source of trivalent metal ions constituting the basic layer.
[0092] In the present invention, as interlayer anion, carbonate ion, nitrate ion, chloride ion, sulfate ion, phosphate ion etc. can be used.When carbonate ion is used as interlayer anion, sodium carbonate is used as supply source.But sodium carbonate can be replaced with the gas that comprises carbon dioxide (carbon dioxide gas), or it can be pure carbon dioxide gas, with the mixture of other gases in fact.For example, the waste gas discharged from the incinerator, coal-fired boiler, heavy oil boiler etc. of paper mill can be suitably used as the gas containing carbon dioxide.In addition, the carbon dioxide produced by the lime calcining process can also be used to carry out carbonation reaction.
[0093] In the synthesis of hydrotalcite, the higher the concentration of the raw materials (metal ions, CO3 ions, etc. constituting the basic layer) in the solution, and the higher the temperature, the easier the nucleation reaction is to proceed. However, under such conditions, when manufacturing composite fibers, it is not easy to fix the nucleus to the cellulose fibers, and it is easy to synthesize inorganic particles free in the suspension. Therefore, in order to manufacture composite fibers firmly bonded to hydrotalcite, it is necessary to properly control the nucleation reaction. Specifically, this can be achieved by rationalizing the concentration of CO3 ions and pulp and smoothing the supply of metal ions per unit time. For example, the CO3 ion concentration in the reaction vessel is preferably 0.01mol / L or more and less than 0.80mol / L. If it is less than 0.01mol / L, the reaction is not easy to proceed. If it is 0.80mol / L or more, it is easy to synthesize inorganic particles free in the suspension. The pulp concentration is preferably 0.5% or more and less than 4.0%. If it is less than 0.5%, the frequency of collision between the raw material and the fiber is reduced, so the reaction is not easy to proceed. If it is more than 4.0%, a uniform composite cannot be obtained due to poor stirring. The supply rate of metal ions per unit time also depends on the type of metal. For example, in the case of Mg ions, it is preferably 0.001 mol / min or more and less than 0.010 mol / min per 1L of reaction solution, and more preferably 0.001 mol / min or more and less than 0.005 mol / min. If it is less than 0.001 mol / min, the reaction is not easy to proceed. If it is more than 0.010 mol / min, it is easy to synthesize inorganic particles free in the suspension.
[0094] (Alumina / Silica)
[0095] In the case of synthesizing alumina and / or silica, the synthesis method of alumina and / or silica can utilize a known method. In the case of using any one or more of an inorganic acid or an aluminum salt as the starting material for the reaction, an alkali silicate is added for synthesis. It is also possible to use an alkali silicate as a starting material and add any one or more of an inorganic acid or an aluminum salt for synthesis, but in the case of using an inorganic acid and / or an aluminum salt as a starting material, the product is well fixed to the fiber. As an inorganic acid, there is no particular limitation, for example, sulfuric acid, hydrochloric acid, nitric acid, etc. can be used. Among these, sulfuric acid is particularly preferred from the viewpoint of cost and operation. As an aluminum salt, aluminum sulfate, aluminum chloride, polyaluminum chloride, alum, potassium alum, etc. can be mentioned, among which aluminum sulfate can be appropriately used. As an alkali silicate, sodium silicate or potassium silicate, etc. can be mentioned, and sodium silicate is easy to obtain, so it is preferred. The molar ratio of silicic acid to alkali may be arbitrary. Generally, the product circulated as No. 3 silicic acid is sodium silicate having a molar ratio of SiO2:Na2O=3 to 3.4:1, and the product can be used appropriately.
[0096] In the present invention, when producing composite fibers in which silica and / or alumina are attached to the fiber surface, it is preferred to synthesize silica and / or alumina on the fiber while maintaining the pH of the reaction solution containing the fiber at 4.6 or less. The details of the reason why composite fibers in which the fiber surface is well coated are obtained by this are not yet completely clear, but it is believed that by maintaining the pH low, the ionization rate to trivalent aluminum ions becomes high, so that composite fibers with high coating rate and fixing rate can be obtained.
[0097] In the synthesis of silica and / or alumina, the higher the concentration of the raw materials (silicate ions, aluminum ions) in the reaction solution, and the higher the temperature conditions, the easier the nucleation reaction is to proceed. However, in the case of manufacturing composite fibers, under such conditions, it is not easy to fix the nucleus to the cellulose fiber, and it is easy to synthesize inorganic particles free in the suspension. Therefore, in order to manufacture composite fibers to which silica and / or alumina are firmly bonded, it is necessary to properly control the nucleation reaction. Specifically, this can be achieved by rationalizing the pulp concentration and smoothing the supply of added silicate ions and aluminum ions per unit time. For example, the pulp concentration is preferably 0.5% or more and less than 4.0%. If it is less than 0.5%, the frequency of collision between the raw material and the fiber is reduced, so the reaction is not easy to proceed. If it is 4.0% or more, a uniform composite cannot be obtained due to poor stirring. The supply rate per unit time of the added silicate ion and aluminum ion is preferably 0.001mol / min or more per 1L reaction solution in the case of aluminum ion, more preferably 0.01mol / min or more, and in addition, preferably less than 0.5mol / min, more preferably less than 0.050mol / min. If less than 0.001mol / min, the reaction is difficult to proceed, and if more than 0.050mol / min, inorganic particles free in the suspension are easily synthesized.
[0098] As a preferred embodiment, the average primary particle size of the inorganic particles in the composite fiber of the present invention can be, for example, 1.5 μm or less, but the average primary particle size can also be 1200 nm or less, 900 nm or less, and further, the average primary particle size can also be 200 nm or less, 150 nm or less. In addition, the average primary particle size of the inorganic particles can also be 10 nm or more. It should be noted that the average primary particle size can be measured using an electron microscope photograph.
[0099] (Aluminum Hydroxide)
[0100] Aluminum hydroxide is an ionic crystalline compound composed of aluminum ions and hydroxide ions represented by Al(OH)3. It is mostly in the form of particles and is poorly soluble in water. Synthetic products obtained through chemical reactions are used as pharmaceuticals and adsorbents, and are also used as flame retardants and non-flammable agents by releasing water when heated.
[0101] In the present invention, a composite of aluminum hydroxide and fiber can be produced by synthesizing aluminum hydroxide in a solution in the presence of fiber. For example, a method of reacting an acid (sulfuric acid, etc.) with an alkali by neutralization, or reacting an inorganic salt with an acid or an alkali, or reacting inorganic salts with each other can be cited. For example, aluminum hydroxide can be obtained by reacting sodium hydroxide with aluminum sulfate, or aluminum hydroxide can be precipitated by adding aluminum chloride to an aqueous solution containing an alkali salt.
[0102] In the synthesis of aluminum hydroxide, the higher the concentration of the raw materials (Al ions, OH ions) in the solution, and the higher the temperature, the easier the nucleation reaction is to proceed. However, in the case of manufacturing composite fibers, under such conditions, it is not easy to fix the nucleus to the cellulose fiber, and it is easy to synthesize inorganic particles free in the suspension. Therefore, in order to manufacture composite fibers firmly bonded with aluminum hydroxide, it is necessary to properly control the nucleation reaction. Specifically, this can be achieved by rationalizing the concentration of OH ions and pulp and smoothing the supply of Al ions per unit time. For example, the OH ion concentration in the reaction vessel is preferably 0.01 mol / L or more and less than 0.50 mol / L. If it is less than 0.01 mol / L, the reaction is not easy to proceed. If it is 0.50 mol / L or more, it is easy to synthesize inorganic particles free in the suspension. The pulp concentration is preferably 0.5% or more and less than 4.0%. If it is less than 0.5%, the frequency of collision between the raw material and the fiber is reduced, so the reaction is not easy to proceed. If it is 4.0% or more, a uniform composite cannot be obtained due to poor stirring. The supply rate of Al ions per unit time is preferably 0.001 mol / min or more and less than 0.050 mol / min per 1 L of the reaction solution. If it is less than 0.001 mol / min, the reaction is difficult to proceed, while if it is 0.050 mol / min or more, inorganic particles free in the suspension are easily synthesized.
[0103] fiber
[0104] The composite fiber used in the present invention is obtained by composite cellulose fiber and inorganic particles. As the cellulose fiber constituting the composite, for example, natural cellulose fiber can be used, and regenerated fibers (semi-synthetic fibers) such as rayon and lyocell, synthetic fibers, etc. can also be used without restriction. As the raw material of cellulose fiber, pulp fiber (wood pulp, non-wood pulp), cellulose nanofiber, bacterial cellulose, cellulose from animals such as sea squirts, algae, etc. can be exemplified, and wood pulp can be manufactured by pulping wood raw materials. Examples of the wood raw material include coniferous trees such as red pine, black pine, fir, spruce, red pine, larch, Japanese fir, hemlock, Japanese cedar, Japanese cypress, larch, white fir, fish-scale spruce, cypress, Douglas fir, Canadian hemlock, white fir, spruce, balsam fir, cedar, pine, southern pine, and radiata pine, and mixed materials thereof; and broad-leaved trees such as Japanese beech, birch, Japanese alder, oak, red nanmu, chestnut, white birch, black poplar, poplar, ash, sweet poplar, eucalyptus, mangrove, eucalyptus, acacia, and mixed materials thereof.
[0105] The method of pulping natural materials such as wood raw materials (wood raw materials) is not particularly limited, and examples thereof include pulping methods generally used in the papermaking industry. Wood pulp can be classified according to the pulping method, for example, chemical pulp obtained by cooking using methods such as the kraft method, the sulfite method, the caustic soda method, and the polysulfide method; mechanical pulp obtained by pulping using mechanical forces such as refiners and grinders; semi-chemical pulp obtained by pulping using mechanical forces after pretreatment with chemical reagents; waste paper pulp; deinked pulp, etc. Wood pulp may be in an unbleached state (before bleaching) or a bleached state (after bleaching).
[0106] Examples of non-wood-derived pulp include cotton, hemp, sisal, abaca, flax, straw, bamboo, bagasse, kenaf, sugarcane, corn, rice stalks, Broussonetia papyrifera (Palm Tree), and Daphne koreana.
[0107] The pulp fibers may be unbeaten or beaten, and the selection may be made according to the physical properties of the composite sheet, but are preferably beaten, because this can be expected to improve the strength of the sheet and promote the fixation of the inorganic particles.
[0108] In addition, these cellulose raw materials can also be used as powdered cellulose, chemically modified cellulose such as oxidized cellulose, and cellulose nanofibers: CNF (microfibrillated cellulose: MFC, TEMPO-oxidized CNF, phosphated CNF, carboxymethylated CNF, mechanically pulverized CNF, etc.) by further processing. As the powdered cellulose used in the present invention, for example, a rod-shaped crystalline cellulose powder with a certain particle size distribution produced by a method such as purifying, drying, pulverizing, and screening the undecomposed residue obtained by acid hydrolysis of selected pulp can be used, and commercial products such as KC FLOCK (manufactured by Nippon Paper Industries), CEOLUS (manufactured by Asahi Kasei Chemicals), and Avicel (manufactured by FMC Corporation) can also be used. The degree of polymerization of cellulose in the powdered cellulose is preferably about 100 to 1500, the crystallinity of the powdered cellulose measured by X-ray diffraction is preferably 70 to 90%, and the volume average particle size measured by a laser diffraction particle size distribution analyzer is preferably 500nm to 100μm.
[0109] The oxidized cellulose used in the present invention can be obtained, for example, by oxidation in water using an oxidant in the presence of a compound selected from an N-oxyl radical compound and a bromide, an iodide or a mixture thereof. As cellulose nanofibers, a method of defibration of the above-mentioned cellulose raw material can be used. As a defibration method, for example, the following method can be used: a water suspension of chemically modified cellulose such as cellulose and oxidized cellulose is subjected to mechanical grinding or beating to defibrate using a fine grinder, a high-pressure homogenizer, a grinder, a single-axis or multi-axis kneading machine, a bead mill, etc. The above methods can also be combined in one or more combinations to produce cellulose nanofibers. The fiber diameter of the manufactured cellulose nanofibers can be confirmed by electron microscopic observation, for example, preferably in the range of 5nm to 300nm. When producing the cellulose nanofibers, any compound can also be further added before and / or after the cellulose is defibrated and / or micronized to react with the cellulose nanofibers to produce cellulose with modified hydroxyl groups. Examples of the functional group to be modified include acetyl, ester, ether, ketone, formyl, benzoyl, acetal, hemiacetal, oxime, isonitrile, allene, thiol, urea, cyano, nitro, azo, aryl, aralkyl, amino, amide, imide, acryloyl, methacryloyl, propionyl, propioloyl, butyryl, 2-butyroyl, valeryl, hexanoyl, heptanoyl, octanoyl, nonanoyl, decanoyl, undecanoyl, dodecanoyl, myristoyl, palmitoyl, stearyl, octanoyl, succino ... Acyl groups such as acyl, pivaloyl, benzoyl, naphthoyl, nicotinoyl, isonicotinoyl, furoyl, cinnamoyl, etc., isocyanate groups such as 2-methacryloyloxyethyl isocyanato, methyl, ethyl, propyl, 2-propyl, butyl, 2-butyl, tert-butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, dodecyl, myristyl, palmityl, stearyl, alkyl groups such as oxirane, oxetane, oxy, thiirane, thiirane, etc. The hydrogen in these substituents can be replaced by functional groups such as hydroxyl and carboxyl. In addition, a part of the alkyl group can also be an unsaturated bond. There is no particular limitation on the compounds used to introduce these functional groups, and examples thereof include compounds having a group from phosphoric acid, compounds having a group from carboxylic acid, compounds having a group from sulfuric acid, compounds having a group from sulfonic acid, compounds having an alkyl group, compounds having a group from amine, etc. The compound having a phosphate group is not particularly limited, and examples thereof include phosphoric acid, lithium salts of phosphoric acid such as lithium dihydrogen phosphate, dilithium hydrogen phosphate, trilithium phosphate, lithium pyrophosphate, and lithium polyphosphate. Further examples thereof include sodium salts of phosphoric acid such as sodium dihydrogen phosphate, disodium hydrogen phosphate, trisodium phosphate, sodium pyrophosphate, and sodium polyphosphate. Further examples thereof include potassium salts of phosphoric acid such as potassium dihydrogen phosphate, dipotassium hydrogen phosphate, tripotassium phosphate, potassium pyrophosphate, and potassium polyphosphate. Further examples thereof include ammonium salts of phosphoric acid such as ammonium dihydrogen phosphate, diammonium hydrogen phosphate, triammonium phosphate, ammonium pyrophosphate, and ammonium polyphosphate.Among these, from the viewpoint of high efficiency of introducing phosphate group and easy industrial application, phosphoric acid, sodium salt of phosphoric acid, potassium salt of phosphoric acid, ammonium salt of phosphoric acid are preferably used, and sodium dihydrogen phosphate and disodium hydrogen phosphate are more preferably used, which are not particularly limited. As the compound with carboxyl group, it is not particularly limited, and dicarboxylic acid compounds such as maleic acid, succinic acid, phthalic acid, fumaric acid, glutaric acid, adipic acid, itaconic acid, and tricarboxylic acid compounds such as citric acid and aconitic acid can be cited. As the acid anhydride of the compound with carboxyl group, it is not particularly limited, and the acid anhydride of dicarboxylic acid compounds such as maleic anhydride, succinic anhydride, phthalic anhydride, glutaric anhydride, adipic anhydride, itaconic anhydride can be cited. As the derivative of the compound with carboxyl group, it is not particularly limited, and the imide of the acid anhydride of the compound with carboxyl group and the derivative of the acid anhydride of the compound with carboxyl group can be cited. As the imide of the acid anhydride of the compound with carboxyl, it is not particularly limited, and the imide of dicarboxylic acid compounds such as maleimide, succinimide, and phthalimide can be cited. As the derivative of the acid anhydride of the compound with carboxyl, it is not particularly limited. For example, at least a part of the hydrogen atoms of the acid anhydride of the compound with carboxyl such as dimethyl maleic anhydride, diethyl maleic anhydride, diphenyl maleic anhydride can be cited. The compound is substituted by a substituent (such as an alkyl group, a phenyl group, etc.). Among the above-mentioned compounds with groups from carboxylic acids, maleic anhydride, succinic anhydride, and phthalic anhydride are preferably used from the aspects of easy industrial application and easy gasification, and are not particularly limited. In addition, even if chemical bonding is not performed, the cellulose nanofiber can be modified in the form of physical adsorption of the modified compound on the cellulose nanofiber. As the physically adsorbed compound, a surfactant can be cited, and any one of anionic, cationic, and nonionic can be used. When the above modification is performed before cellulose is defibrated and / or pulverized, these functional groups can also be separated and restored to the original hydroxyl groups after defibration and / or pulverization. By implementing the above modification, the defibration of cellulose nanofibers can be promoted, or the cellulose nanofibers can be easily mixed with various substances when used.
[0110] The fiber shown above can be used alone or mixed with multiple uses. For example, the fibrous material reclaimed from the drainage of a paper mill can also be supplied to carbonation reaction of the present invention. By supplying such material in the reaction tank, various composite particles can be synthesized, and in addition, fibrous particles etc. can also be synthesized in shape.
[0111] In the present invention, in addition to fibers, materials that are introduced into inorganic particles as a product to generate composite particles can also be used. In the present invention, fibers represented by pulp fibers are used, but in addition to these, inorganic particles, organic particles, polymers, etc. can be synthesized in a solution containing inorganic particles to produce composite particles that further incorporate these materials.
[0112] The fiber length of the composite fiber is not particularly limited, and the average fiber length may be about 0.1 μm to 15 mm, 1 μm to 12 mm, 100 μm to 10 mm, 400 μm to 8 mm, etc. In the present invention, the average fiber length is preferably 400 μm or more (0.4 mm or more).
[0113] The average fiber diameter of the composite fiber is not particularly limited, and for example, the average fiber diameter may be about 1 nm to 100 μm, or may be 500 nm to 100 μm, 1 μm to 90 μm, 3 μm to 50 μm, 5 μm to 30 μm, etc. Among them, in the present invention, if the average fiber diameter is 500 nm or more, the production efficiency of the subsequent process can be improved, and thus it is preferred.
[0114] The average fiber length and average fiber diameter of the fibers can be measured by a fiber length measuring device. Examples of the fiber length measuring device include Valmet Fractionator (manufactured by Valmet Corporation).
[0115] The composite fiber is preferably used in an amount in which more than 15% of the fiber surface is covered with inorganic particles. For example, the weight ratio of the fiber to the inorganic particles can be 5 / 95 to 95 / 5, or 10 / 90 to 90 / 10, 20 / 80 to 80 / 20, 30 / 70 to 70 / 30, or 40 / 60 to 60 / 40.
[0116] In a preferred embodiment, the composite fiber of the present invention has 15% or more of the fiber surface covered with inorganic particles. When the cellulose fiber surface is covered with such an area ratio, the characteristics attributed to the inorganic particles are significantly produced, while the characteristics attributed to the fiber surface are reduced.
[0117] The composite fiber of the present invention can be used in various forms, for example, it can be made into powder, granules, molds, aqueous suspensions, pastes, sheets, plates, blocks, and other forms. In addition, the composite fiber can be used as a main component together with other materials to form a mold, granules, and other molded bodies. There is no particular limitation on the dryer used when drying to make a powder, for example, an airflow dryer, a belt dryer, a spray dryer, etc. can be appropriately used.
[0118] The composite fiber of the present invention can be used for various purposes, for example, it can be widely used for paper, fiber, cellulose composite material, filter material, coating, plastic or other resin, rubber, elastomer, ceramic, glass, tire, building material (asphalt, asbestos, cement, plate, concrete, brick, tile, plywood, fiberboard, ceiling material, wall material, floor material, roof material, etc.), furniture, various carriers (catalyst carrier, medicine carrier, pesticide carrier, microorganism carrier, etc.), adsorbent (impurity removal, deodorization, dehumidification, etc.), antibacterial material, antiviral agent, anti-wrinkle agent, clay, grinding material, friction material, modifier, repair material, heat insulation material, heat resistant material, heat dissipation material, moisture-proof material, waterproof material, water-resistant material, shading material, sealant, shielding material, insect repellent, adhesive, medical material, paste material, anti-discoloration agent, electromagnetic wave absorbing material, insulating material, sound insulation material, interior material, vibration-proof material, semiconductor sealing material, radiation shielding material, material, etc. In addition, it can be used for various fillers, coating agents, etc. in the above-mentioned uses. Among them, adsorbents, antibacterial materials, antiviral agents, friction materials, radiation shielding materials, flame retardant materials, building materials, and thermal insulation materials are preferred.
[0119] The composite of the present invention can be applied to papermaking, for example, printing paper, newspaper, inkjet paper, PPC paper, kraft paper, high-grade paper, coated paper, micro-coated paper, wrapping paper, tissue paper, color high-grade paper, cast-coated paper, carbonless paper, label paper, thermal paper, various fancy papers, water-soluble paper, release paper, craft paper, wallpaper base paper, flame-retardant paper (non-combustible paper), laminate base paper, printed electronic paper, battery separator, buffer paper, tracing paper, etc. Paper, impregnated paper, ODP paper, building material paper, cosmetic material paper, envelope paper, tape paper, heat exchange paper, chemical fiber paper, sterilization paper, water-resistant paper, oil-resistant paper, heat-resistant paper, photocatalytic paper, cosmetic paper (oil-absorbing paper, etc.), various toilet papers (toilet paper, facial tissue, wiping paper, diapers, sanitary products, etc.), tobacco paper, board paper (mounting paper, core paper, white board paper, etc.), paper plate base paper, cup base paper, baking paper, sandpaper, synthetic paper, etc. That is, according to the present invention, a composite of inorganic particles and fibers with a small primary particle size and a narrow particle size distribution can be obtained, so that different characteristics from the previous inorganic fillers with a particle size of more than 2 μm can be exerted. Furthermore, unlike the case where the inorganic particles are simply combined in the fiber, when the inorganic particles and the fiber are pre-composite, a sheet in which the inorganic particles are not only easily retained on the sheet, but also uniformly dispersed without agglomeration can be obtained. In a preferred embodiment, the inorganic particles in the present invention are not only fixed to the outer surface of the fiber and the inside of the lumen, but also generated inside the microfibers, which was confirmed by the results of electron microscopic observation.
[0120] In addition, when using the composite fiber of the present invention, particles and various fibers generally referred to as inorganic fillers and organic fillers can be used together. For example, as inorganic fillers, calcium carbonate (light calcium carbonate, heavy calcium carbonate), magnesium carbonate, barium carbonate, aluminum hydroxide, calcium hydroxide, magnesium hydroxide, zinc hydroxide, clay (kaolin, calcined kaolin, layered kaolin), talc, zinc oxide, zinc stearate, titanium dioxide, silicon dioxide made from sodium silicate and inorganic acid (white carbon, silicon dioxide / calcium carbonate composite, silicon dioxide / titanium dioxide composite), white clay, bentonite, diatomaceous earth, calcium sulfate, zeolite, inorganic fillers obtained by regenerating the ash obtained from the deinking process and inorganic fillers that form a composite with silicon dioxide and calcium carbonate during the regeneration process, etc. As calcium carbonate-silicon dioxide composites, in addition to calcium carbonate and / or light calcium carbonate-silicon dioxide composites, amorphous silicon dioxide such as white carbon can also be used in combination. As organic fillers, urea-formaldehyde resins, polystyrene resins, phenolic resins, tiny hollow particles, acrylamide complexes, materials from wood (fine fibers, microfiber fibers, powdered kenaf), modified insoluble starch, ungelatinized starch, etc. can be cited. As fibers, natural fibers such as cellulose can certainly be used, and synthetic fibers artificially synthesized from raw materials such as petroleum, as well as regenerated fibers (semi-synthetic fibers) such as rayon and lyocell, and inorganic fibers, etc. can also be used without restriction. As natural fibers, in addition to the above, protein fibers such as wool, silk, collagen fibers, and composite sugar chain fibers such as chitin·chitosan fibers and alginate fibers can be cited. As raw materials of cellulose, pulp fibers (wood pulp, non-wood pulp), bacterial cellulose, cellulose from animals such as sea squirts, and algae can be exemplified. Wood pulp can be manufactured by pulping wood raw materials. As the wood raw material, there can be exemplified conifers such as red pine, black pine, fir, spruce, red pine, larch, Japanese fir, hemlock, Japanese cedar, Japanese cypress, larch, white fir, fish-scale spruce, cypress, Douglas fir, Canadian hemlock, white fir, spruce, balsam fir, cedar, pine, pine, radiata pine, and mixed materials thereof, and broad-leaved trees such as Japanese beech, birch, Japanese alder, oak, red nanmu, chestnut, white birch, black poplar, poplar, ash, sweet poplar, eucalyptus, mangrove, eucalyptus, acacia, and mixed materials thereof. The method for pulping the wood raw material is not particularly limited, and pulping methods generally used in the papermaking industry can be exemplified. Wood pulp can be classified according to the pulping method, for example, chemical pulp obtained by cooking by the kraft process, sulfite process, caustic soda process, polysulfide process, etc.; mechanical pulp obtained by pulping by mechanical force of refiners, grinders, etc.; semi-chemical pulp obtained by pulping by mechanical force after pretreatment with chemical reagents; waste paper pulp; deinked pulp, etc. Wood pulp can be in an unbleached state (before bleaching) or a bleached state (after bleaching).As pulp from non-wood, cotton, hemp, sisal, Manila hemp, flax, straw, bamboo, bagasse, kenaf, sugarcane, corn, rice stalks, papyrus chinensis (grape pan), yellow daphne, etc. can be exemplified. Wood pulp and non-wood pulp can be any one of unbeaten and beaten. In addition, these cellulose raw materials can also be used as chemically modified cellulose such as powdered cellulose, oxidized cellulose, and cellulose nanofibers: CNF (microfibrillated cellulose: MFC, TEMPO oxidized CNF, phosphated CNF, carboxymethylated CNF, mechanically crushed CNF) by further processing. As synthetic fibers, polyesters, polyamides, polyolefins, acrylic fibers can be cited, as semi-synthetic fibers, rayon, acetate fibers, etc. can be cited, as inorganic fibers, glass fibers, carbon fibers, various metal fibers, etc. can be cited. For the above components, they can be used alone or in combination of two or more.
[0121] The average particle size and shape of the inorganic particles constituting the composite fiber of the present invention can be confirmed by observation using an electron microscope. Furthermore, by adjusting the conditions for synthesizing the inorganic particles, inorganic particles having various sizes and shapes can be composited with the fiber.
[0122] Example
[0123] The present invention will be described in more detail below with reference to Examples, but the present invention is not limited to such Examples. In addition, in this specification, unless otherwise specified, concentrations, parts, etc. are by weight, and numerical ranges are described in a form including their endpoints.
[0124] Experiment 1: Synthesis and evaluation of composite fibers
[0125] 1-1. Composite fiber of zinc-based hydrotalcite and fiber (samples a and b)
[0126] A solution for synthesizing hydrotalcite (Zn-based HT) was prepared. As an alkaline solution (Solution A), a mixed aqueous solution of Na2CO3 (Fujifilm Wako Pure Chemical Industries, Ltd.) and NaOH (Fujifilm Wako Pure Chemical Industries, Ltd.) was prepared. Also, as an acid solution (Solution B), a mixed aqueous solution of ZnSO4 (Fujifilm Wako Pure Chemical Industries, Ltd.) and Al2(SO4)3·16H2O (Fujifilm Wako Pure Chemical Industries, Ltd.) was prepared.
[0127] Alkaline solution (Solution A, Na2CO3 concentration: 0.05M, NaOH concentration: 0.8M)
[0128] ·Acid solution (B solution, Zn system, ZnSO4 concentration: 0.9M, Al2(SO4)3·16H2O concentration: 0.15M)
[0129] Cellulose fibers were used as composite fibers, specifically pulp fibers containing bleached kraft pulp of broadleaf trees (LBKP, manufactured by Nippon Paper Industries, Ltd., fiber width 20 μm) and bleached kraft pulp of coniferous trees (NBKP, manufactured by Nippon Paper Industries, Ltd., fiber width 50 μm) at a weight ratio of 8:2 and adjusted to a Canadian standard freeness of 300 ml using a single disc refiner (SDR).
[0130] An alkaline solution is added to pulp fibers to prepare an aqueous suspension containing pulp fibers (pulp fiber concentration: 3.0%, pH: about 12.8). The aqueous suspension (pulp solid content 20 kg) is placed in a 1000 L reaction vessel, and an acid solution is added dropwise while stirring the aqueous suspension to synthesize a composite fiber of hydrotalcite particles and fibers. Figure 1 The reaction temperature was 50°C, and the dropwise addition was stopped when the pH of the reaction solution reached about 7.5. After the dropwise addition was completed, the reaction solution was stirred for 30 minutes for aging. The aged sample was dehydrated with a centrifugal dehydrator, and 2 to 10 times the amount of water was further added, and the dehydration was repeated until the conductivity reached 100 mS / m or less to wash the composite fiber.
[0131] 1-2. Composite fiber of barium sulfate and fiber (sample c)
[0132] Pulp fibers (LBKP:NBKP=8:2) whose Canadian standard freeness was adjusted to 300 ml were used in the same manner as in Sample a.
[0133] Barium hydroxide octahydrate (Fujifilm Wako Pure Chemical Industries, Ltd.) was added to pulp fibers to prepare an aqueous suspension containing pulp fibers (pulp fiber concentration: 3.0%, pH: about 12.5). The aqueous suspension (pulp solid content 20 kg) was placed in a 1000 L reaction vessel, and sulfuric acid (Fujifilm Wako Pure Chemical Industries, Ltd., prepared as a 2% aqueous solution) was added dropwise while stirring the aqueous suspension to synthesize a complex of barium sulfate particles and fibers. Figure 1 The reaction temperature is 50°C, and the dropwise addition is stopped when the pH of the reaction solution reaches about 7.5. After the dropwise addition is completed, the reaction solution is stirred for 30 minutes, and then washed with 10 times the amount of water to remove salt. Then, dehydration is performed using a centrifugal dehydrator, and 2 to 10 times the amount of water is further added, and dehydration is repeated until the conductivity reaches 100 mS / m or less to wash the composite fiber.
[0134] 1-3. Composite fiber of copper-containing zinc-based hydrotalcite and fiber (sample d)
[0135] Pulp fibers (LBKP:NBKP=8:2) adjusted to a Canadian standard freeness of 300 ml were used in the same manner as in Sample a.
[0136] In the synthesis of copper-containing zinc-based hydrotalcite (Cu-containing Zn-based HT), a mixed aqueous solution of Na2CO3 (Fujifilm Wako Pure Chemical Industries, Ltd.) and NaOH (Fujifilm Wako Pure Chemical Industries, Ltd.) was prepared as an alkaline solution (Solution A). In addition, a mixed aqueous solution of three chemical reagents, namely, ZnSO4 (Fujifilm Wako Pure Chemical Industries, Ltd.), CuSO4 (Wako Pure Chemical Industries, Ltd.), and Al2(SO4)3·16H2O (Fujifilm Wako Pure Chemical Industries, Ltd.), was prepared as an acid solution (Solution C).
[0137] Alkaline solution (Solution A, Na2CO3 concentration: 0.05M, NaOH concentration: 0.8M)
[0138] ·Acid solution (C solution, ZnSO4 concentration: 0.75M, CuSO4 concentration: 0.15M, Al2(SO4)3·16H2O concentration: 0.15M)
[0139] A composite fiber was synthesized in the same manner as in Sample a except that the above-mentioned chemical reagent was used, and the aged sample was dehydrated with a centrifugal dehydrator to wash the composite fiber.
[0140] 1-4. Composite fiber of copper-containing zinc-based hydrotalcite and PET fiber (sample e)
[0141] Composite fibers were synthesized in the same manner as sample d except that polyethylene terephthalate fibers (PET, fiber diameter: 1.7 dtex, fiber length: 5 mm) were used as fibers, and the aged sample was dehydrated with a centrifugal dehydrator to wash the composite fibers.
[0142] 1-5. Composite fiber of titanium oxide and magnesium hydrotalcite fiber (sample f)
[0143] Pulp fibers (LBKP:NBKP=8:2) whose Canadian standard freeness was adjusted to 300 ml were used in the same manner as in Sample a.
[0144] In the synthesis of magnesium-based hydrotalcite (Mg-based HT), a mixed aqueous solution of MgSO4 (Fujifilm Wako Pure Chemical Industries, Ltd.) and Al2(SO4)3·16H2O (Fujifilm Wako Pure Chemical Industries, Ltd.) is prepared as an alkaline solution (A solution) and an acid solution (D solution).
[0145] Alkaline solution (Solution A, Na2CO3 concentration: 0.15M, NaOH concentration: 2.4M)
[0146] Acid solution (Solution D, MgSO4 concentration: 0.9M, Al2(SO4)3·16H2O concentration: 0.15M)
[0147] Pulp fibers are added to an alkaline solution to prepare an aqueous suspension containing pulp fibers (pulp fiber concentration: 2.0%, pH: about 12.7). 3.5 kg of titanium dioxide (R-3L, manufactured by Sakai Chemical Industry Co., Ltd.) is added to the aqueous suspension (3 kg of pulp solid content) and stirred thoroughly. While stirring the aqueous suspension, an acid solution is added dropwise to a reaction temperature of 50°C, and the addition is stopped when the pH of the reaction solution reaches about 7. After the addition is completed, the reaction solution is stirred for 30 minutes, and then washed with 10 times the amount of water to remove salt. Then, dehydration is performed using a centrifugal dehydrator, and 2 to 10 times the amount of water is further added. Dehydration is repeated until the conductivity reaches 100 mS / m or less to wash the composite fibers.
[0148] 1-6. Evaluation of composite fibers
[0149] The composite fiber samples were evaluated based on the following procedure.
[0150] (1) Surface coverage
[0151] The obtained composite fiber (sample a: Figure 2 , sample b: Figure 3 , sample c: Figure 4 , sample d: Figure 5 , sample f: Figure 6 ). About 70% of the fiber surface of any sample was covered with inorganic particles.
[0152] (2) Moisture content (water content)
[0153] The sample was dried at 105° C. for 2 hours, and the water content was calculated from the weight loss due to drying. In addition, the solid content (concentration) is “100-water content”.
[0154] (3) Weight ratio of fiber to inorganic particles
[0155] The ash content of the composite fiber was measured for the sample dried at 105° C. for 2 hours in accordance with JIS P 8251:2003, and the weight ratio of the fiber constituting the composite fiber to the inorganic particles was calculated.
[0156] [Table 1]
[0157]
[0158] Experiment 2: Preparation and evaluation of pellets containing composite fibers
[0159] 2-1. Production of pellets containing composite fibers
[0160] (Sample 1)
[0161] Granules are manufactured using sample a as a raw material. Specifically, sample a (water content: about 70%) is put into a professional shear mixer (WB type, Pacific Machinery) and stirred at room temperature. Next, steam is added to the professional shear mixer to make the temperature inside the device above 80°C, and the mixture is dried while stirring. Drying is performed until the water content reaches about 10%, and then granulation is performed while adding water (finished product particle size after granulation: about 0.5 mm, water content after granulation: about 50%). Use a 0.5 mesh sieve to finally obtain granules with a particle size of less than 0.5 mm.
[0162] (Sample 2)
[0163] Granulation was performed in the same manner as in Sample 1 except that Sample b was used as the raw material. Granules of 0.5 to 1.0 mm were finally obtained using a 0.5 to 1.0 mesh sieve.
[0164] (Sample 3)
[0165] The pellets of Sample 2 were air-dried for 72 hours to produce pellets having a moisture content of 20%.
[0166] (Sample 4)
[0167] Pellets were produced in the same manner as in Sample 3 except that Sample a was used as the raw material.
[0168] (Sample 5)
[0169] Granulation was performed in the same manner as in Sample 2 except that Sample b was used as a raw material and the final particle size after granulation was 1.0 mm. Granules having a particle size of 1.0 to 3.0 mm were finally obtained using a sieve of 1.0 to 3.0 mesh.
[0170] (Sample 6)
[0171] The pellets of Sample 5 were air-dried for 72 hours to produce pellets having a moisture content of 20%.
[0172] (Sample 7)
[0173] Pellets were produced in the same manner as in Sample 5 except that Sample a was used as the raw material.
[0174] (Sample 8)
[0175] Granulation was performed in the same manner as in Sample 3 except that Sample b was used as a raw material and the final particle size after granulation was 3.0 mm. Granules having a particle size of 3.0 to 4.0 mm were finally obtained using a sieve of 3.0 to 4.0 mesh.
[0176] (Sample 9)
[0177] Sample b (water content: about 70%) was dried until the water content reached 10% or less, and then further pulverized using a chopper until the size was less than 0.5 mm. The treated sample was added to a tumble granulator (CF-360N, Freund Industries), and granulated while adding water (finished product particle size after granulation: about 1.0 mm, water content after granulation: about 20%). A 1.0 to 3.0 mesh sieve was used to finally obtain particles with a particle size of 1.0 to 3.0 mm.
[0178] (Sample 10)
[0179] The production was carried out in the same manner as in Sample 3 except that Sample c was used as the raw material.
[0180] (Sample 11)
[0181] The production was carried out in the same manner as in Sample 2 except that Sample d was used as the raw material.
[0182] (Sample 12)
[0183] The production was carried out in the same manner as in Sample 2 except that Sample e was used as the raw material.
[0184] (Sample 13)
[0185] The production was carried out in the same manner as in Sample 2 except that Sample f was used as the raw material.
[0186] (Sample 14: Comparative Example)
[0187] The water content of sample b was adjusted to about 70% using a Buchner funnel to prepare a sample.
[0188] (Sample 15: Comparative Example)
[0189] Water was added to 100 g of powdered cellulose (trade name: W-50, manufactured by Nippon Paper, average particle size: 40 μm) and stirred and mixed, and then the wet powder (water content: about 5%) was granulated while adding water using a tumbling granulator (finished particle size after granulation: about 1 mm, water content after granulation: about 35%). The obtained granulated material was sieved to obtain particles with a particle size of 0.5 to 1.0 mm.
[0190] 2-2. Evaluation of particles
[0191] The samples were evaluated based on the following evaluation procedures.
[0192] (1) Water content (moisture content) and weight ratio of inorganic components
[0193] The moisture content (%) was measured in the same manner as in Experiment 1. The weight ratio (%) of the inorganic component was also measured in the same manner as in Experiment 1 to calculate the weight ratio of the fiber to the inorganic particles.
[0194] (2) Angle of repose (fluidity)
[0195] Using a powder property tester (HOSOKAWA MICRON, Powder Tester PT-X), a powder sample was passed through an attached metal funnel at a vibration scale of 1.5. The powder is dropped and the ridge angle of the mountain formed by the powder is measured using the angle measurement method "Peak Operation" as the repose angle.
[0196] If the angle of repose can be measured, it is evaluated as “fluidity exists”, and if it cannot be measured, it is evaluated as “no fluidity.” It can be said that the lower the value of the angle of repose, the better the fluidity.
[0197] (3) Dispersibility
[0198] Add 90g of sodium chloride and 10g of the sample to a plastic bag (170mm×240mm) and mix manually for 3 minutes. Take 10g from the mixture, add 200ml of distilled water, and use a stirrer to dissolve the sodium chloride. Filter the treated solution using filter paper (JIS P3801, for quantitative analysis, 5 types of B), dry the residue on the filter paper at 50°C for 2 hours, and measure the weight of the particles contained in 10g of the mixture. Calculate the dispersion rate based on the formula "weight of the dried particles / 1g×100", and set 70% or more as qualified (○), and less than 70% as unqualified (×).
[0199] (4) Bulk density
[0200] The mass lightly filled in a certain volume is measured, and the value obtained by dividing by the volume is defined as the "bulk density (relaxed bulk density"). Specifically, the mass of the sample when it is filled to the 1000 mL mark in a 1000 mL measuring cylinder is measured, and the bulk density (g / cm 3 ) value.
[0201] (5) Particle size distribution
[0202] A laser diffraction particle size distribution analyzer (Mastersizer 3000, manufactured by Malvern Panalytical) was used to obtain a volume cumulative 50% particle size (average particle size) from a sample (0.3 to 1.0 g) used for measurement.
[0203] [Table 2]
[0204]
[0205] As is clear from the above table, the granules of the present invention have better fluidity and dispersibility than those not processed into granules.
Claims
1. A particle comprising composite fibers of cellulose fibers and inorganic particles, with a particle size of 0.2 to 4 mm and a moisture content of 20% or more and less than 60%, The average fiber diameter of the cellulose fibers is 3 to 50 μm, and the inorganic particles include: metal salts of calcium, magnesium, barium or aluminum, metal particles including titanium, copper or zinc, or silicates, The weight ratio of cellulose fiber to inorganic particles in the composite fiber is 10 / 90 to 90 / 10.
2. The particles according to claim 1, having an angle of repose of 30 to 58°.
3. The particle according to claim 1 or 2, wherein The inorganic particles include barium sulfate.
4. The particle according to claim 1 or 2, wherein The inorganic particles are hydrotalcite.
5. The particle according to claim 1 or 2, wherein The weight ratio of the inorganic particles in the particles is greater than 10%.
6. The particle according to claim 1 or 2, wherein The cellulose fibers are wood pulp.
7. The particle according to claim 1 or 2, wherein At least 15% of the surface of the cellulose fibers is covered with inorganic particles.
8. The particle according to claim 1 or 2, wherein The weight ratio of cellulose fiber / inorganic particles is 40 / 60 to 60 / 40.
9. A method for producing the particles according to any one of claims 1 to 8, comprising: A process for synthesizing inorganic particles in a liquid containing cellulose fibers to obtain composite fibers, and The process of granulating the composite fibers into particles with a particle size of 0.2 to 4 mm.
10. The method according to claim 9, wherein: In the granulation step, the composite fibers are granulated while being dried.
11. The method according to claim 9, wherein: The composite fibers are granulated after the moisture content is adjusted to 6 to 50%.
12. The method according to claim 9, wherein: The composite fibers are pulverized and then granulated.
Citation Information
Patent Citations
Remedy for hypoferremia and its preparation
JP1985006619A
Flame-retardant composite fiber and method for producing same
WO2019159943A1
Composite of fiber and inorganic particles
CN110023558A
Manufacturing method of fine fibrous cellulose-containing article
JP2017057285A